TI_GERICHTE 52.2016.627 vom 9. November 2016 , Ricorso contro un'ordinanza municipale concernente il servizio taxi - TI Tribunale d'appello (2016)
Ricorso contro un'ordinanza municipale concernente il servizio taxi